KAJIAN STATUS GIZI, POLA JAJAN DAN KEMAMPUAN DAYA TANGKAP SAAT BELAJAR MASA NEW NORMAL PADA SISWA SD - Wahyuni, Islah (MIDWIFERY JOURNAL, 2021)
Background: The nutritional status of students during this pandemic needs to be a concern for schools, in assessing their students' learning abilities. The pandemic that has occurred since the last two years has affected the process of learning life in schools, including in terms of how to realize clean living behavior in schools (PHBS). One of the indicators of PHBS in the school setting is consuming healthy food and efforts to eat healthy snacks, it has become an obligation for the school to facilitate the realization of healthy snack patterns for students. Healthy snacks will affect children's health, children's nutritional intake and nutritional status of school children. The results of initial observations on students of SDN 14 Mandau there are still students who have unhealthy patterns of nutritional intake, like to consume unhealthy snacks on the outskirts of the school, and the students' body stature is thin and the ability to learn is slow and fast.Objective: To determine nutritional status, snack patterns and the ability to capture power while studying at SDN 14 Mandau Mandau Duri Bengkalis Riau school students.Methods: Correlative research with a cross sectional approach using a total sampling technique with a sample of 30 students who have participated in the UKS Training and Establishment. Data was collected using a questionnaire, observing the capture power by giving pretest and posttest questions, physical examination using a checklist.The results  Indicators of the nutritional status of students showed that most of the students had normal height (TB/U) (-3 SD to 2) as many as 23 people (76.7%). Meanwhile, the majority of the nutritional status (BB/U) was good, as many as 27 people (90%). The majority of students' stature (BMI/U) is normal (-2 SD to 1), namely 26 people (86.7%). The indicator of the majority of students' snacks is unhealthy, namely 22 people (73.3%) with the most favorite type of snacks being meatballs / grilled sausages (13 people (43.3%). %)The conclusion is that there are indicators of nutritional status, height, and stature of students as well as snack patterns and the ability to catch students' learning abilities that must be considered by the school and parents at home.Suggestion: This research can be developed for further research, by adding other variables that may have an influence on nutrition on student achievement Keywords: Nutritional Status, Snack Patterns, Capability while studying, Elementary School Students  ABSTRAK Latar belakang:  Status gizi siswa dalam masa pandemi ini perlu menjadi perhatian bagi pihak sekolah, dalam menilai kemampuan belajar siswanya. Pandemi yang terjadi sejak kurang lebih dua tahun terakhir mempengaruhi proses kehidupan pembelajaran disekolah, termasuk dalam hal bagaimana mewujudkan perilaku hidup bersih disekolah (PHBS). Salah satu indikator PHBS di tatatan sekolah  adalah mengkonsumsi makanan sehat dan upaya jajanan sehat, sudah menjadi kewajiban bagi pihak sekolah untuk memfasilitasi terwujudnya pola jajanan yang sehat bagi siswanya. Jajanan sehat akan berpengaruh terhadap kesehatan anak, asupan nutrisi anak serta status gizi anak sekolah. Hasil observasi awal pada siswa SDN 14 mandau masih terdapat siswa yang memiliki pola asupan nutrisi yang kurang sehat, senang mengkonsumsi jajan tidak sehat dipinggiran sekolah, dan adanya perawakan tubuh siswa yang kurus serta daya tangkap belajar yang lambat dan cepat.Tujuan : Mengetahui  Status Gizi, pola jajan dan  kemampuan daya tangkap saat belajar pada siswa sekolah SDN 14 mandau Mandau Duri Bengkalis Riau.Metode: Penelitian corelatif  dengan pendekatan cross sectional menggunakan teknik total sampling dengan sampel 30 responden Siswa yang telah mengikuti Pelatihan dan Pembentukan UKS. Pengumpulan data dilakukan dengan menggunakan kuesioner, pengamatan daya tangkap dengan pemberian soal pretest dan post test, pemeriksaan fisik menggunakan daftar cecklist.Hasil penelitian: Indicator Status gizi siswa didapatkan data bahwa Sebagian besar siswa memiliki tinggi badan (TB/U)  normal  (-3 SD sampai 2) yaitu sebanyak 23 orang (76,7%). Sedangkan status gizi (BB/U) mayoritas baik yaitu sebanyak 27 orang (90%). Perawakan siswa (IMT/U) mayoritas normal (-2 SD sampai dengan 1)  yaitu 26 orang (86,7%). Indikator jajan siswa mayoritas tidak sehat yaitu 22 orang (73,3%)   dengan jenis jajanan yang paling terfavorit adalah bakso / sosis bakar (13 orang (43,3%). Daya tangkap siswa belajar sebagian besar baik  yaitu 19 orang (63,3%)Kesimpulan terdapat Indikator Status gizi, tinggi badan, dan perawakan siswa serta pola jajan dan kemampuan daya tangkap siswa saat belajar yang harus diperhatikan oleh pihak sekolah dan orangtua dirumah.Saran : penelitian ini dapat dikembangkan untuk penelitian selanjutnya, dengan menambahkan variabel lain yang dimungkinkan memiliki pengaruh terhadap gizi terhadap prestasi belajar siswa